An approach to the didactics of physics for structural engineering from an artistic perspective (2020)
The use of physics in structural engineering requires the combination of its logical strength with social sensitivity. Logical strength is provided by mathematics and physics with practical solutions and new thinking relationships. Social sensitivity is achieved by inserting this "hard" knowledge into the solution of community problems. It is desirable that the teaching of physics and its applications prioritize holistic knowledge over mechanicity and that this process be similar to the one followed by the artist when he conceives his work: he dreams it, tries it, feels it, and adjusts and delivers it after having understood it with his whole being. In terms of curriculum, it is advisable to rethink the contents, encourage the use of majeutics, reduce standardization, personalize evaluation, and abolish the belief that there can be useless knowledge.